PERSONAL SELLING DALAM PERSPEKTIF ISLAM - Firmansyah, Fani (Fakultas Ekonomi, UIN Maliki Malang, 2012)
Currently the business world faces a new era of competition is very tight.For example in the trade industry, the strictness of a competition requirescompanies to be more active in promoting its products. By applying the strategy or the right marketing methods, business must be better prepared to deal with that era. Moreover in this era of globalization, appears a new phenomenon of global consumer (global consumers), as a result the company must improve competitiveness to maintain the continuity of their business through various improvements, both in terms of pricing, promotion, product quality, distribution, sales and service strategies . Represent improvements that must be done by a company, in terms of personal selling islami is a method appropriate promotional strategies to achieve corporate objectives in the face of this globalization era. In making a purchase, one will go through several stages of the buying decision process consisting of problem recognition, information search, alternative evaluation, purchase decision and behavior after purchase. With personal selling have direct effects that arise in face-to-face meetings between sellers and buyers, where there is communication of the necessary factors to influence the decision to purchase or use of psychological factors in order to persuade and to give courage to the time of purchase decisions with the goal of keeping the sales transaction